Analisis Pengaruh Work Life Balance dan Kepuasan Kerja terhadap Kesejahteraan Karyawan pada PT. Candra Broadcast Mediantara - Della Anatera Fadhila; Arief Satriansyah (Ebisnis Manajemen, 2025)
This study aims to analyze the influence of Work Life Balance and job satisfaction on employee well-being at PT Candra Broadcast Mediantara. The research was motivated by the increasing work demands in the digital era, which affect employees’ ability to maintain work-life balance and experience job satisfaction—factors that play a critical role in determining employee well-being. This study adopts a quantitative approach with an associative research type. Data were collected through questionnaires distributed to 32 active employees of the company. The data were processed using IBM SPSS Statistics 26. The results showed that, partially, Work Life Balance has a positive and significant effect on employee well-being, with a significance value of 0.024 < 0.05. Similarly, job satisfaction also has a positive and significant effect on employee well-being, with a significance value of 0.035 < 0.05. Simultaneously, Work Life Balance and job satisfaction significantly affect employee well-being, as indicated by a significance value of 0.039. The coefficient of determination indicates that both independent variables jointly contribute 61.7% to employee well-being, while the remaining 38.3% is influenced by other variables outside this study.The implication of this research is the importance for companies to foster a work environment that supports work-life balance and enhances the dimensions of job satisfaction in order to achieve optimal employee well-being.